Pengaruh Latihan Beban Dumbell Terhadap Kemampuan Servis Atas Ekstrakurikuler Bola Voli Putra SMKN 3 Seluma: The effect of dumbell weight tranining on service ability for men’s volleyball extracurricular at SMKN 3 Seluma - M. Alan Yosep Hidayat Saputra; Dian Pujianto; Andika Prabowo (Universitas Bengkulu, 2023)
This study aims to determine the effect of dumbbell weight training on the service ability of volleyball extracurricular at SMKN 3 Seluma. This study refers to a quantitative research approach with the type of research used is an experiment. The population in this study were all male students who took part in volleyball extracurricular at SMKN 3 Seluma, while the sample in this study used total sampling as many as 30 people. The instrument used is a top service eability test. The test results show that there is an effect of dumbbell weight training on the ability to serve up. Hypothesis testing shows the value of t count 9.576 > t table 2.048, so it shows that ho is rejected and ha is accepted, which means that there is a significant effect on increasing the top serviceability after being treated with the dumbbell weight training method.Keywords: Ability, Dumbell, Extracurricular, Volleyball